Allicin alleviates Dextran Sodium Sulfate (DSS)-induced ulcerative colitis in BALB/c mice - Pandurangan, Ashok Kumar; Ismail, Salmiah; Saadatdoust, Zeinab; Mohd Esa, Norhaizan (Hindawi Publishing Corporation, 2015)
The objective of this study is to evaluate the effect of allicin (10mg/kg body weight, orally) in an experimental murine model of UC by administering 2.5% dextran sodium sulfate (DSS) in drinking water to BALB/c mice. DSS-induced mice presented reduced body weight, which was improved by allicin administration. We noted increases in CD68 expression, myeloperoxidase (MPO) activities, and Malonaldehyde (MDA) and mRNA levels of proinflammatory cytokines, such as tumor necrosis factor- (TNF-)